Capital - Energy Substitution: Does Energy Sources Matter for the Elasticity of Substitution? An Empirical Investigation for OECD Countries - Altunç, Ömer Faruk; Yıldırım, Abdulmecit (My University, 2020)
Energy and other factors of production are the primary inputs in the context of sustainable economic growth. This makesenergy relatively strategic in the development stage and in the energy importers economies. In this study, the effect ofelasticity of substitution on economic growth is investigated for 31 OECD countries over the period from 1990-2014.Although the effect of elasticity of substitution between capital and aggregate energy consumption on economic growthhas been examined in many studies, the issue of how this effect changes between the different sources of energy hasnot been adequately addressed. The research is aimed at contributing to the related literature in this regard. The effectof elasticity of substitution between capital and different energy sources on economic growth is examined within theneoclassical Solow-Swan Growth model. In this model, technology is defined by a variable elasticity of substitution (VES)production function. The empirical model is estimated by the non-linear least squares (NLLS) method. The results showthat oil and primary energy consumption are substitutes; natural gas, coal, and hydroelectricity consumption are thecomplement in the final production of output.